Kelayakan Usahatani Nilam di Dusun Labuaja Desa Laiya Kecamatan Cenrana Kabupaten Maros - Firdayanti Firdayanti; Arifin Arifin; Andi Nur Imran (Universitas Muslim Maros, 2021)
Patchouli plant is one of the plants that produce patchouli oil. This study aims to analyze: To determine the production and income of patchouli farming in Labuaja Hamlet, Laiya Village, Cenrana District, Maros Regency and to determine the feasibility of patchouli farming in Labuaja Hamlet, Laiya Village, Cenrana District, Maros Regency. The research was conducted in Labuaja Hamlet, Laiya Village, Cenrana District, Maros Regency from May to July 2020 with a sample size of 15 farmers. The data used are primary data and secondary data. Data were collected from survey results with questionnaires, interviews and field observations. This research uses descriptive quantitative analysis method to determine farm income and farm feasibility. The results of this study indicate that the average fixed cost is Rp. 80,000, the average variable cost is Rp. 1,956,333.33. Revenue in patchouli farming with an average of Rp. 17,866,667. Meanwhile, the average net income for patchouli farmers is Rp. 15,822,333. Feasibility of patchouli farming in Labuaja Hamlet, Laiya Village, Kec. Cenrana, Kab. Maros can be said to be feasible with the R / C Ratio value of 9.